Exploration of Dalit Trauma in Sarad Paudel's Likhe - Magarati, Shyam Lal (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
Dalit community has been suffered in every aspect due to the institutionalized discrimination of the Hindu caste system in Nepal which is also known as the output of the religious and political reasons. This unfair practice has left a clear mark of social division, exclusion and inequality severely ruining Dalits' life and identity. Sarad Paudel addresses this issue and offers a glimpse of being a Dalit or untouchable in his novel Likhe. He narrates episodes of verbal and physical violence; recurrent inter- and intra-caste discrimination, which depicts the traumatic existence of that oppressed community. Other dominations and discriminations are less traumatic in the comparison of the cultural trauma caused by untouchability, which is like an incurable disease. Therefore, the aim of this paper is to examine the Dalit trauma as represented in this novel. To analyze the representation of traumatic experience in Dalits, the researcher has tried to apply the theoretical insights based on Jeffrey C. Alexander, Stuart Hall, Sigmund Freud and Cathy Caruth's exploration on trauma. This paper attempts to reveal how Dalit people have been living in the society bearing harsh torture, trauma and inhuman treatment in the context of Hindu Brahmin dominated society. This study adds new avenue for academic discussion in the field of academia so as to address the age-long discriminatory system in order to create a just and healthy society without any forms of discrimination in the name of race, class caste, color and gender. Therefore, this issue needs further exploration in academic discourse.